Cavity-Containing [Fe2L3]4+ Helicates: An Examination of Host-Guest Chemistry and Cytotoxicity - Lisboa, Lynn S.; Riisom, Mie; Vasdev, Roan A. S.; Jamieson, Stephen M. F.; Wright, L. James; Hartinger, Christian G.; Crowley, James D. (Frontiers in Chemistry, 2021)
Two new di(2,2'-bipyridine) ligands, 2,6-bis([2,2'-bipyridin]-5-ylethynyl)pyridine (L1) and bis(4-([2,2'-bipyridin]-5-ylethynyl)phenyl)methane (L2) were synthesized and used to generate two metallosupramolecular [Fe2(L)3](BF4)4 cylinders. The ligands and cylinders were characterized by elemental analysis, electrospray ionization mass spectrometry, UV-vis, 1H-, 13C- and DOSY-NMR spectroscopies. The molecular structures of the [Fe2(L)3](BF4)4 cylinders were confirmed using X-ray crystallography. Both the [Fe2(L1)3](BF4)4 and [Fe2(L2)3](BF4)4 complexes crystallized as racemic (rac) mixtures of the ΔΔ (P) and ΛΛ (M) helicates. However, 1H NMR spectra showed that in solution the larger [Fe2(L2)3](BF4)4 was a mixture of the rac-ΔΔ/ΛΛ and meso-ΔΛ isomers. The host-guest chemistry of the helicates, which both feature a central cavity, was examined with several small drug molecules. However, none of the potential guests were found to bind within the helicates. In vitro cytotoxicity assays demonstrated that both helicates were active against four cancer cell lines. The smaller [Fe2(L1)3](BF4)4 system displayed low μM activity against the HCT116 (IC50 = 7.1 ± 0.5 μM) and NCI-H460 (IC50 = 4.9 ± 0.4 μM) cancer cells. While the antiproliferative effects against all the cell lines examined were less than the well-known anticancer drug cisplatin, their modes of action would be expected to be very different.